Kebijakan Pemerintah Orde Lama, Orde Baru,dan Era Reformasi Terhadap Pendidikan Islam - debi yandrizal; Zulmuqim; Fauza Masyhudi (Journal of International Multidisciplinary Research, 2023)
One part of public policy is education policy. A policy arises because there is a problem that requires appropriate handling, so that the policy can be used as a guide. Formulating education policy is a process of formulating reforms for actions that are relevant and acceptable to common sense to resolve various problems related to education. This research uses qualitative methods and is included in the library research category. The data sources were obtained from primary books and journals related to the theme, the data analysis technique used descriptive analytical methods. The results of this research include: that the first time Islamic education was in the motherland was in line with the arrival of Islam to Indonesia. Through long dynamics there are three phases. First, during the Old Order the government slowly paid attention to Islamic education. Second, in the new order, during this period madrasas achieved equality with public schools. In the third period of reform, Islamic education in this period has developed advanced, the curriculum, then Islamic education is also paid attention to by disbursing a budget of 20% of the APBN.